2019
DOI: 10.1002/pri.1798
|View full text |Cite
|
Sign up to set email alerts
|

Group‐based, individualized, comprehensive core stability and balance intervention provides immediate and long‐term improvements in walking in individuals with multiple sclerosis: A randomized controlled trial

Abstract: ObjectivesWalking impairments are common in individuals with multiple sclerosis. Trunk control is a prerequisite for walking; however, knowledge regarding whether core stability and balance training influence walking is limited. This study aimed to investigate the immediate and long‐term effects of a group‐based, individualized, comprehensive core stability and balance intervention (GroupCoreDIST) compared with those of standard care on walking.MethodsThis assessor‐blinded, prospective randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 64 publications
2
47
0
Order By: Relevance
“…Another 93 potential articles were removed after the title and abstract review. Forty-five full texts were reviewed, and twenty articles [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] were used in the analysis based on inclusion and exclusion criteria. Figure 1 shows the PRISMA selection process flow chart [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 93 potential articles were removed after the title and abstract review. Forty-five full texts were reviewed, and twenty articles [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] were used in the analysis based on inclusion and exclusion criteria. Figure 1 shows the PRISMA selection process flow chart [24].…”
Section: Resultsmentioning
confidence: 99%
“…Significant improvement compared with physician care [30] or with 1-h massage [38] • No significant differences between Pilates and rebound therapy [45] or aquatic therapy [47] Gait • Significant improvement [28,31,32,34,[36][37][38]40,43,44] • Significant improvement compared with standard physiotherapy care [31] or with home relaxation exercises [32] • No significant improvement [42] • Significant improvement in standardized exercises group compared to Pilates group [43] Physical-functional conditions • No significant improvement in post-intervention Pilates group, but there was in aerobic exercise group [42] (no difference between groups)…”
mentioning
confidence: 99%
“…Moreover, whilst reduction in walking capacity occurs over time (years) in pwMS and preferentially in vulnerable subgroups, 35,36 it rarely becomes detectable within a time span of three to six months. 37 Future longitudinal (ranging from months to years) studies should help establish the trajectory of walking capacity across MS patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…devices, especially when they are less invasive in day-to-day situations and provide real-time feedback. 8,9 Currently, there are two randomised controlled trials (RCTs) 10,11 that have utilised wearable technology in people with multiple sclerosis (PwMS); however, there are several more RCTs currently ongoing that utilise wearable technology, for example, the MD3001 (SPI2) trial. 12 The advantages and disadvantages of wearable technology are summarised in Table 1 above.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that patients, caregivers and health care professionals find value in using such devices, especially when they are less invasive in day-to-day situations and provide real-time feedback. 8 , 9 Currently, there are two randomised controlled trials (RCTs) 10 , 11 that have utilised wearable technology in people with multiple sclerosis (PwMS); however, there are several more RCTs currently on-going that utilise wearable technology, for example, the MD3001 (SPI2) trial. 12 …”
Section: Introductionmentioning
confidence: 99%